Cannabis (Cannabis sativa or C. indica) agriculture and the environment: a systematic, spatially-explicit survey and potential impacts. (21st April 2016) - Butsic, Van; Brenner, Jacob C
Abstract: Cannabis agriculture is a multi-billion dollar industry in the United States that is changing rapidly with policy liberalization. Anecdotal observations fuel speculation about associated environmental impacts, and there is an urgent need for systematic empirical research. An example from Humboldt County California, a principal cannabis-producing region, involved digitizing 4428 grow sites in 60 watersheds with Google Earth imagery. Grows were clustered, suggesting disproportionate impacts in ecologically important locales. Sixty-eight percent of grows were >500 m from developed roads, suggesting risk of landscape fragmentation. Twenty-two percent were on steep slopes, suggesting risk of erosion, sedimentation, and landslides. Five percent were <100 m from threatened fish habitat, and the estimated 297 954 plants would consume an estimated 700 000 m 3 of water, suggesting risk of stream impacts. The extent and magnitude of cannabis agriculture documented in our study demands that it be regulated and researched on par with conventional agriculture.